GmRAV confers ecological adaptation through photoperiod control of flowering time and maturity in soybean. Issue 1 (4th June 2021) - Wang, Yuhe; Xu, Chongjing; Sun, Jiafan; Dong, Lidong; Li, Minmin; Liu, Ying; Wang, Jianhui; Zhang, Xiaoming; Li, Dongmei; Sun, Jingzhe; Zhang, Yuntong; Shan, Jinming; et al.
Abstract: Photoperiod strictly controls vegetative and reproductive growth stages in soybean ( Glycine max ). A soybean GmRAV ( Related to ABI3/VP1 ) transcription factor containing both AP2 and B3 domains was shown to be a key component of this process. We identified six polymorphisms in the GmRAV promoter that showed significant association with flowering time and maturity of soybean in one or multiple environments. Soybean varieties with minor polymorphism exhibited a longer growth period contributing to soybean adaptation to lower latitudes. The cis-acting element GT1CONSENSUS motif of the GmRAV promoter controlled the growth period, and the major allele in this motif shortened duration of late reproductive stages by reducing GmRAV expression levels. Three GmRAV-overexpressing ( GmRAV-ox ) transgenic lines displayed later ﬂowering time and maturity, shorter height and fewer numbers of leaves compared with control plants, whereas transgenic inhibition of GmRAV expression resulted in earlier ﬂowering time and maturity and increased plant height. Combining DNA affinity purification sequencing and RNA sequencing analyses revealed 154 putative target genes directly bound and transcriptionally regulated by GmRAV. Two GmRAV binding motifs [C(A/G)AACAA(G/T)A(C/T)A(G/T)] and [C(T/A)A(C)C(T/G)CTG] were identiﬁed, and acting downstream of E3E4, GmRAV repressed GmFT5a transcriptional activity through binding a CAACA motif, thereby delaying soybean growth and extending both vegetative and reproductive phases. Abstract : A key photoperiod repressor delays flowering time and maturity period in soybean.